2016
DOI: 10.1371/journal.pone.0154232
|View full text |Cite
|
Sign up to set email alerts
|

Initial Effects of Differently Treated Biogas Residues from Municipal and Industrial Wastes on Spring Barley Yield Formation

Abstract: Soil application of biogas residues (BGRs) is important for closing nutrient cycles. This study examined the efficiency and impact on yields and yield formation of solid-liquid separated residues from biodegradable municipal and industrial wastes (bio-waste) in comparison to complete BGRs, nitrification inhibitor, agricultural BGRs, mineral fertilizer and unfertilized plots as control. The experiment was set up as a randomized block design on silt loam Cambisol. Biogas residues from four biogas plants were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Biogas residues contain high levels of plantavailable nutrients (N, P, K) and a considerable amount of organic carbon, which explains their widespread usage in agriculture for closing nutrient cycles (Möller, 2015;Tambone et al, 2010). Several studies have demonstrated the benefits of the agricultural use of BGRs for soil (Nkoa, 2014;Prays and Kaupenjohann, 2016). Anaerobic digestion transforms approximately 20-95% of the carbon in the feedstock into gaseous carbon compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biogas residues contain high levels of plantavailable nutrients (N, P, K) and a considerable amount of organic carbon, which explains their widespread usage in agriculture for closing nutrient cycles (Möller, 2015;Tambone et al, 2010). Several studies have demonstrated the benefits of the agricultural use of BGRs for soil (Nkoa, 2014;Prays and Kaupenjohann, 2016). Anaerobic digestion transforms approximately 20-95% of the carbon in the feedstock into gaseous carbon compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Biogas residues are usually applied as fertilizers to return nitrogen, carbon, and other nutrients to the soil. The effects of BGR application on crop yield, soil chemical, physical and microbial properties have been studied in small-scale experiments (Fouda et al, 2013;Sänger et al, 2014) and short-term field experiments (Prays and Kaupenjohann, 2016;Terhoeven-Urselmans et al, 2009). Nevertheless, there is still little information available on the long-term effects of BGR on soil organic carbon (SOC) (Möller, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BGRs contain high levels of plant-available nutrients (N, P, K) and a considerable amount of organic carbon, which explains their widespread usage in agriculture for closing nutrient cycles [ 4 , 5 ]. Several studies have demonstrated the benefits of the agricultural use of BGRs for yields and soil fertility [ 6 , 7 ]. Anaerobic digestion may transform 20–95% of the carbon in the feedstock into gaseous carbon compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Biogas residues are usually applied as fertilizers to return nitrogen, carbon, and other nutrients to the soil. The effects of BGR application on crop yield, soil chemical, physical and microbial properties have been studied in small-scale experiments (Fouda, von Tucher, Lichti, & Schmidhalter, 2013;Sänger, Geisseler, & Ludwig, 2014) and short-term field experiments (Prays & Kaupenjohann, 2016;Terhoeven-Urselmans, Scheller, Raubuch, Ludwig, & Joergensen, 2009).Nevertheless, there is still little information available on the long-term effects of BGR on soil organic carbon(SOC) (Möller, 2015). Odlare et al (2011)observed an increase in SOC after eight years of BGR application compared to a control treatment.…”
Section: Introductionmentioning
confidence: 99%